2014
DOI: 10.5455/ijmsph.2013.031020131
|View full text |Cite
|
Sign up to set email alerts
|

Role of HRCT temporal bone in pre operative evaluation of choesteatoma

Abstract: Background: Cholesteatoma is potentially dangerous condition as it can extend and erode into adjacent structures and can cause various serious complications. HRCT temporal bone very clearly depicts the anatomy of various small important structures in middle and inner ear cavity. Hence it is an excellent modality and investigation of choice in diagnosing and defining the extent of cholesteatoma. It has become essential investigation in preoperative planning for surgeon. Present study shows good correlation of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 7 publications
5
28
1
Order By: Relevance
“…Incus was more frequently involved followed by malleus and stapes. Similar observations were echoed in the study carried out by Shah et al [18], (incus 85.7 %, malleus 45.7 %, and stapes 31.4 %). Gomma et al [10] noted that the incus was the most commonly eroded, in 88.2 % of patients, followed by malleus, in 67.9 %.…”
Section: Ossicular Erosion and Pneumatization: A Correlationsupporting
confidence: 89%
See 1 more Smart Citation
“…Incus was more frequently involved followed by malleus and stapes. Similar observations were echoed in the study carried out by Shah et al [18], (incus 85.7 %, malleus 45.7 %, and stapes 31.4 %). Gomma et al [10] noted that the incus was the most commonly eroded, in 88.2 % of patients, followed by malleus, in 67.9 %.…”
Section: Ossicular Erosion and Pneumatization: A Correlationsupporting
confidence: 89%
“…Josilito et al [14] in study of 62 patients found erotion incus in 75 % malleus in 40.64 % and stapes in 65.62 %. As it is evident from observations of above investigators [10,18,26,27], in the chronic inflammatory process of middle ears, it is incus which bears the brunt. Among the 58 ears only incus involvement in 15 ears (25.86 %), malleus and incus involvement in 25 (43.10 %) ears, all the three ossicular involvement in 17 ears (29.31 %) was observed.…”
Section: Ossicular Erosion and Pneumatization: A Correlationmentioning
confidence: 87%
“…HRCT accurately diagnosed cholesteatoma in 91% of cases with good sensitivity and specificity based on the presence of non-dependent tissue mass in epitympanum, mastoid antrum and Prussack's space and scutum or ossicular erosion. Chintan Shah et al 11 and Mafee et al identified aditus ad antrum widening with loss of its figure of 8 appearances with mastoid antrum expansion also added value. Swartz et al 12 reported that out of 54 patients with cholesteatoma ossicular erosion was found only in 50% of cases in both by imaging and intraoperatively.…”
Section: Discussionmentioning
confidence: 96%
“…75% of cases with sigmoid plate dehiscence were accurately detected by HRCT with relatively lower sensitivity when compared to other studies. Chintan Shah et al 11 , reported sensitivity and specificity of HRCT in detecting sigmoid erosion to be 91.7% and 95.25% respectively. Sonika Kanotra et al 15 , reported the sensitivity, specificity, positive and negative predictive value to be 100%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation